Penerapan Sistem Olah Tanah dan Pemulsaan Pada Tebu untuk Pengendalian Nematoda Parasit Tumbuhan Dominan - I G. Swibawa; S. P. Yulistiara; T. N. Aeny (Politeknik Negeri Lampung., 2015)
Conventional tillage system practices for a long time can reduce soil qualities because of soil erosion, soil compaction and depleting of soil organic matter. Conservation tillage such as No-tillage system can be applied as an alternative technique to rehabilitate soil degradation problems.. This research is a part of a long term study of soil rehabilitation that was conducted from 2010 till now, in PT GMP, Central Lampung. Sampling of nematodes was done on April 2013 when the second ratoon RGM 00-838 variety of sugarcane was 9 months old. The aim of this research was to study the effect of tillage and mulching systems on the abundance of several dominant plant parasitic nematodes. Split plot experimental design was applied on this research. Tillage system as the main plots consisted of intensive tillage and no-tillage systems, while mulching system as the sub-plots consisted of no-mulch and mulching with 80 ton ha-1 of fresh bagasee. Nematodes were collected from 0-20 cm deep of soil and extracted by sieving and centrifugation with sugar solution methods at the Plant Pest and Disease Laboratory, University of Lampung. The results of this research showed that there were eleven plant parasitic and seven free-living nematode genera inhabited the PT GMP sugarcane plantation. The three plant parasitic nematode genera dominant were Hoplolaimus, Xiphinema, and Hemicriconemoides. No-tillage system effectively reduce the abundance of Xiphinema and , mulching with bagasse reduced the abundance of Hemicriconemoides. Meanwhile, mulching on No-tillage system more effective to reducing the abundance of Hoplolaimus compared to intensive tillage system. This results suggested that the No-tillage with bagasse mulching system was one of alternative techniques to control plant parasitic nematodes pest of sugarcane plantation. Keywords : Tillage, mulching, sugarcane, plant parasitic nematodes, abundance.